GATE-LEXEMES IN THE LANGUAGE OF SLAVIC MASS MEDIA (Philological Studies, 2019)
The article examines some dynamic processes in Slavic languages on the basis of prevailing in mass media gate-lexemes – the words with the international component gate- in the meaning of ‘scandal’. There have been identified some common regularities and specific mechanisms of cultural appropriation of a gate- element. The suffixoid gate- in Slavic mass media is a mark of globalization and newsworthiness. The investigated element demonstrates the greatest productivity in Russian, Ukrainian, Czech, and Polish languages. А vocabulary of Slavic languages enlarges by interlingual (Моникагейт/Monicagate/Monicagate) and intralingual (Янаевгейт/Vychodilgate) gate-lexemes; intralingual units are usual. The article also observes interslavic and German linguistic borrowings of the gate-lexemes. The derivatives with the component gate- are formed by a cognitive metonymic model where the first component means an object (бръмбаргейт), a participant (Begergate), a place (Челябинск-гейт) of a scandal.
Keywords: gate-element, gate-lexemes, language of Slavic mass media